(untitled) (European Journal of Pure and Applied Mathematics, 2026)
Fuzzy differential equations have attracted the attention of many researchers. Based on a hybrid block method, we present a numerical approach for solving first-order fuzzy initial value problems. We investigate the proposed method theoretically and establish convergence and stability results. Two numerical examples are presented to illustrate the efficiency of the proposed method and to compare the results with those obtained by other methods in the literature.